Informational Efficiency in Developing Equity Markets - McDermott, C. (IMF Working Papers; Working Paper ;, 1995)
The issue of informational efficiency in the evolution of asset prices is examined using data on equity markets in Jordan, Turkey and Pakistan over the period 1986-93. The analysis is carried out in two steps. The parameters of agents' dynamic consumption and investment decisions are first estimated, and then the implied equity market price, based on market fundamentals, is compared with the actual evolution of equity market prices. While the informational efficiency of each of the three markets is found to be deficient, the causes of market inefficiency are varied. For Jordan it appears that a large negative shock to economic activity in the late 1980s caused agents to discount market fundamentals. For Turkey and Pakistan it is likely that institutional and legal rigidities in equity and banking markets resulted in these markets being illiquid, although this lack of market depth did reduce in severity for Turkey over the sample period, as liberalization of financial markets occurred.